Pengembangan media pembelajaran berbasis Scrapbook dari kertas bekas untuk meningkatkan kreativitas peserta didik - Syakuro, Abdan; Shalihah, Maratus; Fadhila Safitri, Nida; Kusuma Listiani, Salma; Rahmawati, Ferida (Jurnal Pendidikan Agama Islam, 2025)
This study discusses the development of scrapbook-based learning media from used paper as a strategy to enhance student creativity. The background of this research is based on the low utilization of creative media in learning and the high accumulation of paper waste in schools, necessitating an innovation that is affordable, environmentally friendly, and educational. The scrapbook media concept was developed by integrating the principles of constructivism, social constructivism, experiential learning, and project and multimodality approaches, so that the learning process becomes active, creative, and contextual. The development procedure was carried out through needs analysis, design, prototyping, validation, field trials, and final revision. The assessment strategy used a creativity rubric, process observation, portfolios, and self-assessment to measure aspects of fluency, flexibility, originality, and elaboration of students' ideas. The results of the study indicate that scrapbook media from used paper is effective in encouraging students' creativity, active involvement, collaboration, and ecological awareness, making this media an innovative, fun, and sustainable learning alternative.